Knowledge and Acceptability of Cervical Cancer Screening Among Ante-natal Women in A Tertiary Health Institution in North-Central Nigeria - Changkat Lohnan, Lucky; Oboyi Eneadanu, Salome; Momoh, Mary Christiana; Dogara Bure, Bawa; Yonah Warit, Esther (International Journal of Scientific Research and Management (IJSRM), 2025)
Background: Cervical cancer is the most common female cancer in the developing countries. Worldwide, about half a million women acquire the disease annually and about two-third are from the developing countries. The high rate of prevalence with its associated morbidity and mortality in our environment has made cervical cancer a public health problem. Fortunately, it is a preventable cancer and screening can lead to detection of premalignant lesion and early stage of the disease thus preventing its occurrence and reducing the morbidity and mortality associated with the condition. This study was undertaken to assess the knowledge and acceptance of cervical cancer screening among women attending antenatal clinic at the Federal Medical Centre, Makurdi, North Central Nigeria. Methods: This study was a cross-sectional survey of 345 among women attending antenatal clinic at the Federal Medical Centre, Makurdi, North Central Nigeria. The Knowledge and willingness to accept cervical screening by these women were assessed using a self- administered structured questionnaire.7 Results:Three hundred and forty five (345) women answered the questionnaire and majority of respondents were between the ages of 25-29. Majority, 87(25.2%) were housewives. 176(51.0%) had secondary education while 105(30.4%) had tertiary education. This study revealed that majority of the respondents has a substantial awareness and knowledge of Cervical Cancer screening (68.4%). While 47.5% were ready to undergo Cervical Cancer screening and 66.1% will tell their family members to go for screening. Conclusion: As the knowledge and acceptability of cervical cancer screening was high, more facilities could be made available, accessible, and affordable. Also, health education to improve awareness of cervical cancer screening among antenatal women can improve awareness and uptake of the screening procedure.